Kinerja Sistem Informasi Akuntansi yang dipengaruhi oleh Kemampuan Teknik Personal, Kecanggihan Teknologi Informasi dan Kepuasan Pengguna - Neni Nurhayati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine and analyze the effect of personal technical ability, information technology, and AIS user satisfaction on AIS performance in all offices in Kuningan Regency either simultaneously or partially. The research method used is descriptive and verification methods. The research population is in all offices in Kuningan Regency as many as 18 offices in Kuningan Regency. Calculation of the sample using the slovin formula so that the sample is obtained as many as 74 respondents. Then the sampling was carried out using probability sampling technique with simple random sampling technique. The data collection technique uses a questionnaire distributed to all offices in Kuningan Regency. The results showed that personal technical ability, information technology, and AIS user satisfaction had a simultaneous and significant effect on AIS performance. AIS user satisfaction, personal technical ability, information technology, and AIS user satisfaction partially have a positive and significant effect on AIS performance.